Fine-tuning electroconvulsive therapy: A cognitive comparison of brief and ultra-brief pulse widths - Vishesh Yadav; Abhishek Pathak; Rahul Singh; Jaymin Maganbhai Pandav; Divya Kushwaha; Manish Singh; Yogi Rana (Asian Journal of Medical Sciences)
Background: Electroconvulsive therapy (ECT) has been a cornerstone in managing severe psychiatric illnesses. However, concerns about its cognitive side effects have led to evolving techniques aimed at minimizing cognitive impairments. Specifically, the use of ultra-brief pulse width (0.5 ms) compared to brief pulse width (1.5 ms) in bitemporal modified ECT (MECT) offers a promising avenue for cognitive preservation.